2022
DOI: 10.3390/app122110755
|View full text |Cite
|
Sign up to set email alerts
|

TrojanDetector: A Multi-Layer Hybrid Approach for Trojan Detection in Android Applications

Abstract: Trojan Detection—the process of understanding the behaviour of a suspicious file has been the talk of the town these days. Existing approaches, e.g., signature-based, have not been able to classify them accurately as Trojans. This paper proposes TrojanDetector—a simple yet effective multi-layer hybrid approach for Trojan detection. TrojanDetector analyses every downloaded application and extracts and correlates its features on three layers (i.e., application-, user-, and package layer) to identify it as either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Currently, malware is using sophisticated approaches for cyber attacks and advances its attacking techniques from file-based to fileless attacks to bypass the existing solutions for malware detection [ 13 ]. These existing solutions [ 14 , 15 ] can easily detect file-based malware attacks on windows [ 16 ], Android [ 17 , 18 ], and IoT devices [ 19 ], but fail to detect the fileless malware. This section presents the literature review, and comparative analysis of machine learning approaches limited to fileless malware.…”
Section: Related Workmentioning
confidence: 99%
“…Currently, malware is using sophisticated approaches for cyber attacks and advances its attacking techniques from file-based to fileless attacks to bypass the existing solutions for malware detection [ 13 ]. These existing solutions [ 14 , 15 ] can easily detect file-based malware attacks on windows [ 16 ], Android [ 17 , 18 ], and IoT devices [ 19 ], but fail to detect the fileless malware. This section presents the literature review, and comparative analysis of machine learning approaches limited to fileless malware.…”
Section: Related Workmentioning
confidence: 99%
“…Motivated by the tremendous success of ML techniques in different fields, several ML/DL-based malware detection approaches have been proposed in the recent literature [2,[14][15][16][17][18][19][20]. In this section, we survey the most recent works that adapted machine learning classifiers for malware detection in PE files.…”
Section: Related Workmentioning
confidence: 99%
“…Using k-fold cross-validation on the malware, which includes Trojans and viruses, along with 151 clean files, the authors achieve an overall classification accuracy of 98.86% using the top-performing Decision Tree as the classifier. Finally, in a recent study [20], the authors proposed a multi-layer hybrid approach, namely, TROJANDETECTOR, to detect the Trojan's abnormal behaviour in Android applications from three different Android levels based on the selected features and then apply multiple classifiers for the evaluation. The authors evaluated their scheme on three publicly available datasets and reported that the Support Vector Machine outperformed its counterparts and attained the highest accuracy of 96.64%.…”
Section: Related Workmentioning
confidence: 99%
“…Compared with deep learning models, SVMs are much less computationally demanding as they only have a single activation function, while deep models use multiple activation functions. This characteristic makes SVMs suitable for environments with limited computational resources, such as onboard IoT devices [25]. Liu et al [26] presented a defence system and divided it into three subsystems.…”
Section: Related Workmentioning
confidence: 99%